2013
DOI: 10.1007/s00403-013-1365-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo studies of aquaporins 3 and 10 in human stratum corneum

Abstract: Aquaporins (AQPs) constitute one family of transmembrane proteins facilitating transport of water across cell membranes. Due to their specificity, AQPs have a broad spectrum of physiological functions, and for keratinocytes there are indications that these channel proteins are involved in cell migration and proliferation with consequences for the antimicrobial defense of the skin. AQP3 and AQP10 are aqua-glyceroporins, known to transport glycerol as well as water. AQP3 is the predominant AQP in human skin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…Aquaporin 3 (AQP3) not only transports water but also allows movement of small solutes like glycerol across the plasma membrane (Hara and Verkman, 2003;Hara-Chikuma and Verkman, 2005). In mammalian skin, AQP3 is expressed in the basal layer as well as in the suprabasal layers of the epidermis (Verkman and Mitra, 2000;Hara-Chikuma and Verkman, 2008;Lee et al, 2012;Guo et al, 2013), whereas its presence in the stratum corneum is controversial (Sougrat et al, 2002;Jungersted et al, 2013). Studies characterizing AQP3-knockout mice suggest that this aquaglyceroporin is required for maintaining normal stratum corneum hydration, skin elasticity, wound healing, epidermal biosynthesis, and barrier recovery (Ma et al, 2002;Hara-Chikuma and Verkman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Aquaporin 3 (AQP3) not only transports water but also allows movement of small solutes like glycerol across the plasma membrane (Hara and Verkman, 2003;Hara-Chikuma and Verkman, 2005). In mammalian skin, AQP3 is expressed in the basal layer as well as in the suprabasal layers of the epidermis (Verkman and Mitra, 2000;Hara-Chikuma and Verkman, 2008;Lee et al, 2012;Guo et al, 2013), whereas its presence in the stratum corneum is controversial (Sougrat et al, 2002;Jungersted et al, 2013). Studies characterizing AQP3-knockout mice suggest that this aquaglyceroporin is required for maintaining normal stratum corneum hydration, skin elasticity, wound healing, epidermal biosynthesis, and barrier recovery (Ma et al, 2002;Hara-Chikuma and Verkman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…AQP3 is mostly expressed at the basal layer of the epidermis [46] and its expression is downregulated by UVB irradiation [26, 46]. It is present in both viable and stratum corneum layers of the epidermis [28], thus suggesting the functional role in water transport. Interestingly, the water loss prevention of the stratum corneum is linked to the specific expression of AQP3 between the dermis and basal layers of the epidermis, thus operating as a “water-clamp” to prevent water loss gradient from the dermis to the stratum corneum [47].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen mammalian AQPs have been identified over the last 23 years with differing functions dependent on localization [23]. To date, AQP3, AQP9 and AQP10, called aqua-glycoporins because they transport water, glycerol and possibly other small solutes, have been found in skin [28, 42]. AQP3, the most abundant AQP found in skin, is located in the basal, suprabasal and stratum corneum layers [2, 18, 28, 33, 51] of the epidermis at the cell periphery [47].…”
Section: Introductionmentioning
confidence: 99%
“…Although most reports including this report found that AQP3 is expressed only in strata basale and spinosum in human epidermis, 2,5,6 it was detected in stratum corneum using minimal-invasive technique. 7 Both water and glycerol permeability are remarkably decreased in the epidermis of AQP3-knockout mice, and glycerol transport impairment mainly contribute to reduced stratum corneum hydration and increased TEWL. 2,3 AQP3 overexpression contributes to epidermal hyperplasia, barrier disruption and incremental proinflammatory cytokines in atopic dermatitis.…”
Section: Editormentioning
confidence: 99%
“…Using immunohistochemical technique with anti-AQP3 monoclonal antibody (clone EPR19932, ab215853; 1:500 dilution; Abcam, Cambridge, MA, USA), AQP3 protein expression was detected in lesional and perilesional normal-appearing skin on the wrists of 12 SAK patients (10 males and two females; 20.83 AE 7.69 years, range 7-39) and control skin on the forearms of 14 healthy subjects (seven males and seven females; 26.86 AE 5.95 years, range 15-35). AQP3 expression was assessed by addition of positive percentage of stained cells (<10% = 1; 11-33% = 2; 34-66% = 3; >67% = 4) and staining intensity (weak = 1; moderate = 2; strong = 3) and scored as 1+ (2-3), 2+ (4-5) and 3+ (6)(7). Results were analysed using Kruskal-Wallis and Mann-Whitney tests.…”
Section: Editormentioning
confidence: 99%